Peningkatan Pengetahuan dan Keterampilan Berwirausaha Melalui Pelatihan Pendirian Bisnis Baru - Imas Sukaesih; Aisyah Ratnasari; Khusaini Khusaini (ABDI: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
This training aims to provide knowledge, understanding, and skill to participants about preparing business plans and starting new businesses by utilizing social media. Participants are expected to be able to find breakthroughs in creating job opportunities for themselves and others during the Covid-19 pandemic. This training was attended by 24 participants consisting of members of the Tangerang Mandiri Student Community and housewives. The method of implementing the activities includes the stages of preparation, implementation, and reporting. While the technique of implementing training activities is online. The results of this training activity indicated that the participants were quite satisfied with this training activity. This activity is sufficient to contribute to participants in increasing knowledge, understanding, and skills in establishing new digital-based MSMEs businesses, compiling simple business plans, and being able to find business opportunities. Therefore, in the future, further activities are needed, namely assistance activities for the establishment of new businesses (MSMEs) based on digital and how to design digital marketing using social media.